Evaluating land-cover change and land subsidence in coal fire zones: Insights from multi-source monitoring - Desheng Xie; Fantao Zeng; Baozhu Liu; Quan Fang; Yongwei Dong; He Wu; Peng Liu; Ke Wang; Gensheng Li (PLoS ONE, 2025)
Coal fires are a significant environmental and geological threat, causing extensive ecological damage and loss of resources. Existing monitoring methods, though effective, have limitations in terms of precision and adaptability. This study integrates multiple monitoring techniques, including remote sensing, thermal infrared imaging, UAV based surveys, and field investigations, to assess the environmental and geological consequences of coal fires. The results indicate that: 1) Vegetation cover in the affected regions decreased from 0.43 to 0.38 between 2017 and 2024, with Fire Zone 1 showing minimal recovery and Fire Zone 3 exhibiting moderate improvement, though the overall low vegetation area expanded due to ongoing fires; 2) The Remote Sensing Ecological Index (RSEI) declined from 0.41 to 0.38, with poor-rated areas increasing significantly, particularly in Fire Zone 3, reflecting the ongoing degradation of ecological conditions caused by both fire activity and climate factors; 3) The Flat Spectral Shape Index (FSSI) showed stability, but fluctuations in the areas with moderate and high probability of exposed coal, especially in Fire Zone 3, pointed to the expanding fire footprint and worsening ecological degradation; 4) Surface subsidence varied considerably, with Fire Zone 3 experiencing the most severe subsidence, indicating unstable geological conditions exacerbated by fire activity. The study underscores the importance of continuous monitoring and effective disaster risk management strategies. Despite localized improvements in soil potassium levels, coal fires have caused significant declines in soil nutrients and moisture content. This research contributes to the development of more effective strategies for managing coal fire impacts and supporting ecological restoration efforts in affected regions.